Deep 3D convolutional neural network in early detection of Lung cancer - Hossain, Khandoker Jobayer; Rana, Md. Jewel; Ajghar, Abdullah Ali; Alam, Nur-a-taj (BRAC University, 2019)
Cataloged from PDF version of thesis.